2022
DOI: 10.1103/physreve.105.015210
|View full text |Cite
|
Sign up to set email alerts
|

Stability of two-dimensional complex plasma monolayers in asymmetric capacitively coupled radio-frequency discharges

Abstract: In this article, the stability of a complex plasma monolayer levitating in the sheath of the powered electrode of an asymmetric capacitively coupled radio-frequency argon discharge is studied. Compared to earlier studies, a better integration of the experimental results and theory is achieved by operating with actual experimental control parameters such as the gas pressure and the discharge power. It is shown that for a given microparticle monolayer at a fixed discharge power there exist two threshold pressure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 78 publications
0
16
0
Order By: Relevance
“…In complex plasmas, the electric charge of the grains is obviously a key parameter. Indeed, it determines the interactions of the dust particles with the background ions and electrons and the grain-grain interactions [such as in complex plasma crystals [27,28]]. It is also fundamental in many processes, such as the ion drag force [29,30] and electric charge shielding [31].…”
Section: Introductionmentioning
confidence: 99%
“…In complex plasmas, the electric charge of the grains is obviously a key parameter. Indeed, it determines the interactions of the dust particles with the background ions and electrons and the grain-grain interactions [such as in complex plasma crystals [27,28]]. It is also fundamental in many processes, such as the ion drag force [29,30] and electric charge shielding [31].…”
Section: Introductionmentioning
confidence: 99%
“…The experiments described in this paper were carried out in a modified Gaseous Electronics Conference (GEC) radio-frequency (rf) reference cell 32 . Plasma was pro-duced by a capacitively coupled rf discharge in argon at 13.56 MHz.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…While the additional heating can cause a crystallized monolayer to melt, it also makes it more difficult for particles initially in a fluid state to crystallize. Previous experiments have shown that for microparticle monolayers levitating in the sheath of a rf discharge at a fixed discharge power there are two threshold pressures [21][22][23]: an upper threshold, p crys , above which the monolayer always has a crystalline structure, and a lower threshold, p MCI , below which the monolayer always undergoes MCI causing the monolayer to melt. Between these two pressures, the monolayer can exist in either a crystalline or fluid state depending on the initial state when entering the intermediate pressure regime.…”
Section: Introductionmentioning
confidence: 99%
“…This point charge model for the ion wake adequately represents the system if grains remain far enough apart that the wake charge and location relative to the dust grain are constant [16]. While previous studies have used the point charge model to study MCIs [16,[20][21][22][23][24][25][26][27][28][29], the impact of changing discharge parameters, such as rf power and neutral gas pressure, on the ion wake characteristics remains largely unknown. The nonreciprocal interaction between the dust particles due to ion wakes are also related to other types of phenomena in complex plasma such the Schweigert instability in bi-layer complex plasma crystal [30][31][32][33] or the vertical pairing of dust particles [34].…”
Section: Introductionmentioning
confidence: 99%